Long Non-Coding RNAs Link Oxidized Low-Density Lipoprotein With the Inflammatory Response of Macrophages in Atherogenesis - Yan, Youyou; Song, Dandan; Wu, Junduo; Wang, Junnan (Frontiers in Immunology, 2020)
Atherosclerosis has been characterized as a chronic inflammatory response to cholesterol deposition in arteries. Low-density lipoprotein (LDL), especially the oxidized form (ox-LDL), plays a crucial role in the occurrence and development of atherosclerosis by inducing endothelial cell (EC) dysfunction, attracting monocytes differentiated into macrophages, promoting chronic inflammation. However, the mechanisms linking cholesterol accumulation in macrophage foam cells to inflammation are poorly understood. Long noncoding RNAs (lncRNAs) is a group of non-protein-coding RNAs longer than 200 nucleotides and found to regulate the progress of atherosclerosis. Recently, more and more lncRNAs interfering with the cholesterol deposition or inflammation were found, which might unveil the molecular mechanism or be as novel therapeutic targets. In this review, we summarize and highlight the role of lncRNAs linking cholesterol (mainly ox-LDL) accumulation and inflammation of macrophage during the process of atherosclerosis.